An advanced compliance monitor for patients undergoing brace treatment for idiopathic scoliosis. Issue 2 (February 2015) - Chalmers, Eric; Lou, Edmond; Hill, Doug; Zhao, H. Vicky
Abstract Adolescent idiopathic scoliosis is a spinal deformity affecting 2–3% of adolescents. Brace treatment, the most common non-surgical treatment, uses a hard plastic orthotic shell to prevent progression of the deformity. Previous studies have found association between treatment outcome and patients' compliance with the prescribed brace-wear regimen. However, the exact relationship between compliance and treatment outcome has yet to be elucidated. Current compliance monitoring techniques may not be providing enough information about patients' brace-wear habits. Building on previous work, we present a new compliance monitor which records both temperature and force applied to the patient's body. The combination of temperature and force readings shows both how often and how tightly the brace is worn. The new monitor is designed for minimal size and power consumption, measuring 5.2 cm × 2.5 cm × 0.8 cm, with a battery life of approximately one year. Seven patients wore the monitor in this pilot study. The temperature-based compliance estimate differed significantly from the force-based estimate in four out of seven cases. This suggests that some patients may wear their braces very loosely, and that existing temperature-only or force-only compliance monitors may not be giving a complete picture of brace-wear habits.